ANALYSIS AND EVALUATION OF IMPLEMENTATION OF UNDERGRADUATE NURSING CURRICULLUM FOR FAMILY NURSING IN WEST JAWA - Neti Juniarti; Sheizi Prista Sari; Desy Indra Yani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Nurses are the backbone of the healthcare system, being the key providers of primary healthcare as they comprise 60-80% of the total health workforce, and provide 90% of all heath care services in the primary healthcare arena. This study aimed to evaluate the concordance of family nursing and community health nursing curriculum with international standards and national needs for undergraduate nursing education in West Java.This study used evaluation research design using BEKA framework as a tool to perform curriculum analysis which included Benchmarking, Evidencing, Knowing, and Applying stages. The international standards competency for family nursing and community health nursing, course study guide and samples of students reports were collected and analysed using content analysis. In addition participants from six nursing schools were interviewed to identify application of the curriculums. The results show that some of the competencies outlined in the course study guide were not aligned with international standards of family nursing from International Family Nursing Association. Four dimensional framework of family nursing and community health nursing curriculums were proposed to improve the alignment between international standards as well as local and government needs for family nursing and community health nursing curriculums. School of nursing can apply this framework as guidance to develop their own learning plans based on international standards, national, local and institutional needs. Keywords: curriculum analysis, evaluation, family nursing, community health nursing